Peran Kepala Sekolah dalam Mengoptimalkan Tenaga Kependidikan - Dirahman, Fuad; Setiawan, Farid; Iskandar, Utut Abdillah (Al-DYAS, 2023)
The principal has an essential role in the running of an organization he leads, especially the performance of teachers and education personnel to improve the achievement of their students. The purpose of this paper is to present the role of school principals in optimizing education personnel. The methodology in this writing uses a library approach, while data collection is carried out by examining several journals and books (both in print and electronic form as well as other sources that are considered relevant. The findings in this study are how a school principal plays himself in optimizing educational staff). starting from planning, directing, and supervising all tasks carried out by all school parties, so that it will produce good performance and be able to optimally achieve the school's vision, mission, and goals. The success of learning in a school organization is very dependent on the success of the principal in management of education personnel in schools Optimizing teachers, staff, employees in their work greatly influences school productivity and achievement.